Improving the Role of PD. Pasar Surya in the Supply Chain Strategic Commodity Framework in Surabaya City (Synergizing Local Government Business Units, Private Sectors and Traders) - Hendrati, Ignatia Martha; Nuruni Ika, K. W.; Pudjo, P. Hery; Sishadiyati, Sishadiyati (International Journal of Economics and Financial Issues, 2017)
Food sufficiency is a basic human need so that food availability for the people must always be guaranteed at an affordable price. The increasing public demand has led the price to increase as a result of demand pull inflation. The growing population and economic development has resulted in the degradation, conversion and fragmentation of agricultural land which may ultimately threatens food security that will push up the price of foods. PD. Pasar Surya is one of the business of local government of Surabaya. The unit is expected to have strategic role in supply chain management, so that it can realize price stability and food availability guarantee. This study aims to provide recommendations related to the increasing role of PD. Pasar Surya within the framework of Supply Chain of strategic commodities in Surabaya City. It used SCP Analysis (Structure, Conduct and Performance). Results show that currently the role of PD. Pasar Surya is still limited to the provision of infrastructure facilities and has not accommodated the supply chain management, so that the development of strategic commodity prices is quite volatile with an increasing trend. PD. Pasar Surya is recommended to immediately synergize among all stakeholders through the management of information, goods and services from the earliest suppliers to the latest consumers. Keywords: Supply Chain, PD. Pasar Surya, Food Availability, Price Stability, SCP JEL Classifications: E31, Q18